2020
DOI: 10.1039/d0cy00778a
|View full text |Cite
|
Sign up to set email alerts
|

Alginate–copper microspheres as efficient and reusable heterogeneous catalysts for the one-pot synthesis of 4-organylselanyl-1H-pyrazoles

Abstract: This study demonstrates the facile preparation and use of alginate–Cu2+ microspheres in the catalysis of a new class of organoselenium substituted pyrazoles through one-pot reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…An intrinsic and pivotal characteristic of heterogeneous catalysts and support materials is their stability under harsh reaction conditions and different solvents. [ 43 ] To evaluate the stability of the PEI@PAA and PEI@PAAc/Cu 2+ microparticles, experiments were performed by keeping them under different solvents at high temperatures. The results concerning the weight variation of the microparticles are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…An intrinsic and pivotal characteristic of heterogeneous catalysts and support materials is their stability under harsh reaction conditions and different solvents. [ 43 ] To evaluate the stability of the PEI@PAA and PEI@PAAc/Cu 2+ microparticles, experiments were performed by keeping them under different solvents at high temperatures. The results concerning the weight variation of the microparticles are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…In the work of Souza et al [24], Alg-Cu +2 microspheres were prepared via an ion exchange process, and it was examined as a catalyst for the synthesis of some substituted pyrazoles. The resulted product was in excellent yield, and the catalyst activity still good even after five reactions.…”
Section: Applications Of Alginate Metal Complexes 41 Organic Synthesis Fieldmentioning
confidence: 99%
“…16 Recently, Fajardo and his group have reported a threecomponent reaction for the synthesis of selenoethers of pyrazoles using Cu 2+ immobilized on alginate-based microspheres (Alg−Cu 2+ ) (Scheme 1, eq d). 17 Cheng's research group reported selenylation of uracils in the presence of sodium iodide and H 2 O 2 in dimethyl sulfoxide (DMSO) medium from the reaction of uracil and diselenides (Scheme 1, eq e). 18 Wang et al reported an electrochemical method for the selenylation of uracils in the presence of NH 4 I (Scheme 1, eq f).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Pires et al developed a three-component reaction of benzoylacetonitriles, arylhydrazines, and diaryl diselenides in the presence of molecular iodine as a catalyst (Scheme , eq c) . Recently, Fajardo and his group have reported a three-component reaction for the synthesis of selenoethers of pyrazoles using Cu 2+ immobilized on alginate-based microspheres (Alg–Cu 2+ ) (Scheme , eq d) . Cheng’s research group reported selenylation of uracils in the presence of sodium iodide and H 2 O 2 in dimethyl sulfoxide (DMSO) medium from the reaction of uracil and diselenides (Scheme , eq e) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation